Evaluation Of The Implementation Of Islamic Religious Education Learning In SMPN - Wajdi, Muh Barid NIzarudin; Rahmania, Nurani; Rahman, Mohammad Ibadur (IERA, Islamic Education and Research Academy, 2023)
This study aims to evaluate the implementation of Islamic Religious Education (PAI) at SMPN 1 Ngronggot Nganjuk. The research focuses on describing the application and evaluation processes of PAI in this school. A qualitative method was employed, utilizing interviews, observations, and documentation for data collection. The subjects of this research were Islamic Religious Education teachers at SMPN 1 Ngronggot. The findings indicate that PAI has been effectively implemented and developed to its fullest potential, with the aim of ensuring students can focus on and benefit from the lessons for their future. The study highlights that a professional and well-prepared teacher creates a comfortable learning environment, allowing students to absorb the material more effectively. Conversely, well-behaved students create a conducive teaching environment. The research suggests that teachers should pay closer attention to student discipline to prevent engagement in excessive juvenile delinquency